2017
DOI: 10.5539/ibr.v10n9p60
|View full text |Cite
|
Sign up to set email alerts
|

Determinants and Consequences of Product Differentiation Strategy: Evidence from Chinese Indigenous Exporters

Abstract: Focusing on Chinese indigenous exporters, this research investigates the antecedents of the product differentiation strategy (PDS), and its impacts on export performance with the moderating role of export target markets. Drawing from the contingency theory and strategy management framework, the authors adopt structural equation modeling (SEM) to analyze the survey data collected from 195 Chinese indigenous exporters. The empirical results suggest that the PDS positively affects Chinese exporters' performance. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 27 publications
2
9
1
Order By: Relevance
“…In other words, commercial banks that execute differentiation strategy reap positive financial performance benefits, especially in terms of ROI, as opposed to those that do not execute this kind of strategy. The findings of the present study are consistent with a study that found that the strategy of differentiation was significantly related with the performance of manufacturing firms in Kenya [20]; a study which concluded that differentiation strategy was significantly related with organization performance in terms of Semarang State University [12]; a study which found that product differentiation strategy was significantly associated with export performance in a positive manner in China [21], and one which indicated that service differentiation had a significant impact on creating competitive advantage for Nigerian Railway Corporation particularly in a standardized business environment [10]. This study's findings also support previous research findings indicated that the strategy of differentiation had a significant and positive influence on the performance of hotels in Kano North West in Nigeria [22].…”
Section: Discussion Of Findingssupporting
confidence: 92%
See 1 more Smart Citation
“…In other words, commercial banks that execute differentiation strategy reap positive financial performance benefits, especially in terms of ROI, as opposed to those that do not execute this kind of strategy. The findings of the present study are consistent with a study that found that the strategy of differentiation was significantly related with the performance of manufacturing firms in Kenya [20]; a study which concluded that differentiation strategy was significantly related with organization performance in terms of Semarang State University [12]; a study which found that product differentiation strategy was significantly associated with export performance in a positive manner in China [21], and one which indicated that service differentiation had a significant impact on creating competitive advantage for Nigerian Railway Corporation particularly in a standardized business environment [10]. This study's findings also support previous research findings indicated that the strategy of differentiation had a significant and positive influence on the performance of hotels in Kano North West in Nigeria [22].…”
Section: Discussion Of Findingssupporting
confidence: 92%
“…In China, researchers studied the determinants and consequences of product differentiation strategy using indigenous Chinese exporters as their case study [21]. They specifically sought to find out the predictors of product differentiation strategy and how it impacts on the performance of exports and whether this impact was motivated by export target markets.…”
Section: Empirical Reviewmentioning
confidence: 99%
“…Market expansion strategy stimulates primary demand to help accelerate overall market growth (Walker and Mullins, 2012). Many companies prefer product differentiation when entering new markets because they are constrained by technology and capital reasons (Ju et al , 2017). The differentiation strategy improves company performance in sales growth, export intensity, profitability, level of internationalization and satisfaction with export performance (Lado et al , 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Scope of exceptions can be measured by the geographic scope, sociocultural understanding and continues learning of technological advancements (Zahra et al, 2000). Each company must, therefore, evaluate independently the desirability of each position and select the most appropriate degree of international orientation in light of its own internal situation and objectives (Ju et al, 2017).…”
Section: Sources Of Beneficial Impactmentioning
confidence: 99%
“…Proactiveness enables a firm in attaining new learnings, which increase skill development and competencies (Mathews et al, 2016). Being proactive helps in making timely decisions on IMS, developing products and services as per market demand (Maxwell et al, 2006;Ju et al, 2017).…”
Section: Operational Efficiencymentioning
confidence: 99%